CO2 Emission Assessment Tool for Polar Scientific Fieldwork - Stitelmann, Ólafur Yngvi (Zenodo, 2024)
The purpose of the CO 2 emission assessment tool is to help estimate the carbon footprint of field campaigns, to identify significant emission sources, and to contribute to the development of adequate mitigation strategies of the carbon footprint of polar fieldwork while ensuring scientific quality. Would you be interested in further developing this tool, please contact the Swiss Polar Institute via the following email address: secretariat@swisspolar.ch